PENGARUH YOUTUBE TERHADAP GANGGUAN BERBAHASA ANAK USIA 6-7 - Chandra, Shania Chandra (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2019)
Language is a tool used by humans and speaking is a process used by human compilations. The age of children is a very fast age in English. Intake of this language must be transferred with various factors to prevent interference with children. Disorders that are divided into two namely wernicke aphasia and broca aphasia. To see the problem in this study using descriptive qualitative methods. The aim is to see the disorder in children aged 6-7 years. The findings obtained from this study are disorders experienced by Wernicke's aphasia or motor aphasia, regulating the use of devices in children and practicing speaking and speaking skills in children. Keywords: Language disorders, children?s language, youtube